2014
DOI: 10.1002/mus.24295
|View full text |Cite
|
Sign up to set email alerts
|

Lambert–Eaton syndrome antibodies target multiple subunits of voltage‐gated Ca2+ channels

Abstract: Autoantibodies from LEMS patients bind directly to multiple VGCC α(1) subunits as well as the β(3) subunit. Thus, multiple components of the presynaptic VGCC complex are prospective targets for antibodies in LEMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
(68 reference statements)
0
3
0
3
Order By: Relevance
“…Hajela and coworkers 36 reported that multiple components of the presynaptic VGCC complex are prospective targets for antibodies in LEMS. Autoantibodies from patients with LEMS bind directly to multiple VGCC a1 subunits and the b3 subunit.…”
Section: Diagnosismentioning
confidence: 99%
“…Hajela and coworkers 36 reported that multiple components of the presynaptic VGCC complex are prospective targets for antibodies in LEMS. Autoantibodies from patients with LEMS bind directly to multiple VGCC a1 subunits and the b3 subunit.…”
Section: Diagnosismentioning
confidence: 99%
“…While two studies detected antibodies against VGCC subunit other than alpha-1 in a subset of patients with LEMS [ 142 144 ], no reactivity to the β4 or γ2 auxiliary subunits of VGCC was found in sera from PCD patients in a HEK293 CBA [ 141 ]. However, the authors of the latter study identified in a single patient with SCLC-associated PCD and anti-P/Q-type VGCC a novel autoantibody to the cytoskeletal matrix of the nerve terminals active zone (CAZ) protein ELKS1 (also termed ERC1) [ 141 ], which was recently shown to interact and co-localise with the auxiliary β4 subunit of VGCC [ 145 ].…”
Section: Anti-vgccmentioning
confidence: 99%
“…Menos del 10% de pacientes con SMLE pueden desarrollar degeneración cerebelosa manifestando ataxia, encefalitis límbica y neuropatía sensorial (8,14,15,16). Dentro de las disfunciones autonómicas que se describen se encuentran constipación, alteración pupilomotora, xerostomía, disfunción erectil y anormalidades en la sudoración hasta en un 30% de los pacientes (1,2,5,15,17). Algunos síntomas constitucionales pueden estar presentes como parte de la malignidad subyacente, como lo son pérdida de peso y anorexia (10,16).…”
Section: Presentación Clínicaunclassified
“…Las células cancerígenas sobreexpresan distintos tipos de canales de calcio voltage dependientes, por lo que se cree que en respuesta inmune ante estas células se liberan anticuerpos contra estos canales. Sin embargo los anticuerpos no distiguen entre céulas cancerígenas y células sanas (14,17,19). Estos autoanticuerpos interfieren en la terminal nerviosa motora, rica en canales de calcio voltaje dependientes que participan en la transmisión de la señal nerviosa presináptica hacia el músculo esquelético mediada por acetilcolina, lo que provoca un deterioro de la contracción muscular y por ende provoca la sintomatología del paciente (2,13,15,17,18).…”
Section: Diagnosticounclassified